Fetal Tissues Tested for Microbial Sterility by Culture- and PCR-Based Methods Can be Safely Used in Clinics. Issue 2 (February 2017) - Vitrenko, Yakov; Kostenko, Iryna; Kulebyakina, Kateryna; Duda, Alla; Klunnyk, Mariya; Sorochynska, Khrystyna
Cell preparations to be used in clinical practice must be free of infectious agents. Safety concerns are especially elevated upon the use of human fetal tissues, which are otherwise highly advantageous in cell therapy. We demonstrate that treating fetal samples with antibiotic, extensive washing, and homogenization prior to cryoconservation efficiently removes microbes in general. Screening a large collection by an automatic culture system showed that 89.2% fetal tissue samples were sterile, while contamination was detected in 10.8% samples. Liver and chorion were contaminated more than the brain, kidney, lung, and soft tissues. Broad-range PCR from the bacterial 16s rRNA gene was adopted as a confirmatory assay; however, the concordance between the culture-based and PCR assays was weak. Taxonomic identification was done for contaminated samples by bacteriological methods and sequencing 16s rRNA PCR products. The two approaches revealed different spectra of taxonomic groups sharing only Lactobacillus, the most frequently found genus. In addition, other representatives of vaginal microbiota were detected by culture-based identification, while PCR product sequencing has also revealed a subset of nosocomial microorganisms. Importantly, species known to cause sepsis were identified by both techniques, arguing for their indispensability and mutual complementarity. We suggest that most contaminations are taken up during collection of fetal material rather than originating from an in utero infection. In conclusion, a rigorous microbiological control by culture and PCR is a prerequisite for safe clinical use of fetal tissue suspensions.